Nanofibrils vs nanocrystals bio-nanocomposites based on sodium alginate matrix: An improved-performance study. Issue 2 (February 2020) - Deepa, B.; Abraham, E.; Cordeiro, N.; Faria, M.; Primc, G.; Pottathara, Y.; Leskovšek, M.; Gorjanc, M.; Mozetič, M.; Thomas, S.; Pothan, L.A.
Abstract: To develop bio-nanocomposites using natural biopolymers, nanocomposite films were prepared based on sodium alginate and kapok nanofibrils (CNFs). CNFs when subjected to TEMPO-mediated oxidation gave rise to cellulose nanocrystals (TOCNCs), with carboxyl groups at the surface ( K a / K b = 3.64). The differences between the two types of nanocelluloses (nanofibrils and nanocrystals) and their impact in the preparation of bio-nanocomposites, were studied. When incorporated in the matrix, the CNFs particles have the tendency to form surface aggregation ( K a / K b = 2.37), distorting the alginate network, creating heterogeneous films, with high surface roughness ( S a = 29.37 nm), porosity ( D p = 0.087 cm 2 /min) and vulnerability to heat. The TOCNCs present good dispersion creating a 3D network, which forms uniform ( D p = 0.122 cm 2 /min) and homogeneous films, with smooth surface ( S a = 16.83 nm). The ultrasonication treatment facilitated the dispersion improving the interfacial interaction between the reinforcing phase and the matrix. The results show the reinforcement potential of kapok nanocellulose in an industrially and medically important biopolymer, sodium alginate, especially when TOCNCs and ultrasonication were used. Abstract : Materials science; Nanotechnology; Nanomaterials; Materials characterization; Materials property; Agricultural technology; Nanofibrils; Nanocrystals; TEMPO-Mediated oxidation; Sodium alginate; Kapok fiber; Nanocomposite